Contribution of Meat towards Nutritional Security - An Analysis through Consumption of Different Food Items among Meat and Non-Meat Consumers in Karnataka - Senthilkumar, T; Thirunavukkarasu, M; Muralidhar, V (Journal of Nutrients, 2017)
Human diet and nutritional status have undergone a sequence of major shifts, stated as the nutrition transition. The present study was conducted to explore the contribution of meat towards nutritional security among rural, semi-urban and urban households in Karnataka with the sample size of 90 meat eating respondents and 30 non-meat eating respondents. Conventional analyses like mean and percentages were used for the present study. Apart from these analyses, the calorie and protein intake based on the respondent’s intake of food items of plant source, non-meat animal source and meat animal sources was worked out and discussed. As a whole, calorie and protein intake per consumption unit per day was found high in urban area followed by semi-urban area and awareness on calorie and protein intake among rural area in Karnataka was proposed.